AN ANALYSIS OF CONCRETE NOUN TRANSLATION IN POCKET DICTIONARY ENGLISH-INDONESIA USED IN MOBILE PHONE - Dedy Subandowo (Premise: Journal of English Education and Applied Linguistics, 2012)
This research is intended to find out the total number of meanings and the translation rank shift. This study is a qualitative research. This research is also descriptive research and fact finding. The research object of this study is concrete noun translation and the data are taken from books, electronic devices and internet. The writer uses noting technique to collect the data. To analyze the data, the writer conducts three steps in this research; they are presenting the data, analyzing the data and finding the result of the research.  The result of this study shows that there are three groups of translation meanings; nouns which have one meaning, two meanings and more than two meanings. The translation rank shift is classified into two kinds, the upward rank shift and the downward rank shift. The most frequent type of rank shift is upward rank shift.